PENINGKATAN KEMAMPUAN MENULIS NARASI MELALUI TEKNIK COOPERATIVE INTEGRATED READING AND COMPOSITION - Sudaryo Sudaryo; Edi Suyanto; Nurlaksana Eko Rusminto (Universitas Lampung, 2013)
Writing is a from one of skills language that student should mastered. In the fact the skills write of student is low. Because of that, how to increase writing narrative skills with Cooperative Integrated Reading and Composition (CIRC) technique is a problem in this reseach. Type of research that use is a cualitative descriptive classroom action. This study procedure is permormed three cycles, and each cycle consisted of planning, action, observation, and reflection. Based of the research the conclusion is: (1) learning procces with CIRC techniques can improve activities student. Activities student in classroom VII G first cycle got 71 score. Second cycle 79 and third 82. (2) The average value of narrative writing skills in first cycle got 68.95 score, second cycle got 71.24 score and third cycle got 72.61 score. Mastery learning in first cycle 65%, second cycle got 73% and third cycle got 81%. With CIRC technique can imrove skills writing narrative for student for class VII G in SMP N 3 Natar.Kata kunci: kemampuan menulis narasi, menulis, teknik CIRC.